SELF-DISCLOSURE ON INSTAGRAM: EFFECTS OF NARCISTIC TENDENCIES AND NEEDS FOR AFFILIATION IN UNIVERSITY STUDENTS - Intan Islamia; Nurul Nevi Yanti; Irna Kartina (State Islamic University (UIN) Ar-Raniry, 2023)
Self-disclosure, the act of revealing personal thoughts and emotions to others, is crucial in interpersonal communication. This study investigates the interplay between narcissistic tendencies, the need for affiliation, and self-disclosure among Instagram-utilizing college students. The sample consisted of 93 students selected through purposive sampling. Measurement tools included scales for self-disclosure, narcissistic tendencies, and affiliation needs. The data was analyzed using multiple regression facilitated by JASP software version 0.16.1.0 for Windows. The findings revealed significant associations between narcissistic tendencies, the need for affiliation, and self-disclosure. Specifically, narcissistic tendencies correlated with self-disclosure, yielding a coefficient of (rx1-y) = 0.582 and P < 0.001, contributing to 25.54% of the variance. Furthermore, the need for affiliation demonstrated a relationship with self-disclosure, with a coefficient of (rx2-y) = 0.504 and P < 0.001, contributing to 11.34% of the variance.